Gambaran Tingkat Pengetahuan Ibu Nifas Tentang Pemberian Kolostrum di Wilayah Puskesmas Kubutambahan I Tahun 2024 - Budiarsi, Ni Kadek Rika; Ningtyas, Listina Ade Widya; Ariyani, Ni Wayan (Indonesian Journal Publisher, 2025)
Colostrum is the first fluid secreted by the breast glands, has a thick texture, yellow color, and is high in protein and low in fat. More than 99 infant deaths occurred before the age of 28 days in Buleleng Regency, and almost half were caused by Low Birth Weight (LBW) Babies. The aim of this research is to determine the level of knowledge of postpartum mothers regarding the provision of colostrum in the work area of the Kubucepatn I Community Health Center. The type of research applied in this research is quantitative research with a descriptive research design with a cross sectional design. Implementation in September - November 2024 with a total sampling technique with a total sample of 55 respondents who met the inclusion criteria. The type of data used is primary data using a questionnaire. Data analysis uses univariate. The results of research on 55 respondents showed that the majority with sufficient maternal knowledge were 28 people (50.9%) and the minority with good maternal knowledge was 12 people (21.8%). Conclusion: The knowledge of postpartum mothers about colostrum in the Kubucepatn I Community Health Center area. The majority of mothers' knowledge is sufficient. Postpartum mothers at the Kubucepatn I Community Health Center can increase their knowledge about giving colostrum to newborns by following counseling from health workers or seeking information through mass and electronic media considering the very important benefits of colostrum for baby's health.